Ordered Nanotubular Titanium Disulfide (TiS2) Structures: Synthesis and Use as Counter Electrodes in Dye Sensitized Solar Cells (DSSCs). Issue 5 (2nd November 2018) - Licklederer, Markus; Cha, Gihoon; Hahn, Robert; Schmuki, Patrik
Abstract : TiS2 nanotubular structures were synthesized by a high temperature H2 S treatment of anodized TiO2 nanotube layers, and their electrochemical activity for a use as counter electrodes in dye sensitized solar cells (DSSCs) was evaluated. During conversion to TiS2 compositional, morphological and structural transformations were monitored. The fully converted TiS2 nanostructures show a high electrocatalytic activity for the I − /I3 − oxidation comparable to a nanoparticular platinum layer. For a simplified model a DSSC solar cell efficiency of 6.1% was obtained using the TiS2 nanotube layer as counter electrode, which is very close to values obtained for a Pt reference (6.2%).